1987
DOI: 10.3109/00016348709020750
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Maternal Smoking on Human Fetal Heart Function

Abstract: M-mode echocardiography was used to evaluate fetal heart function following maternal smoking in 21 healthy smoking pregnant women between 24 and 39 weeks of uneventful gestation. Prior to smoking one cigarette (nicotine content 1.7 mg), a fetal M-mode echocardiographic examination was performed and repeated 5 and 10 min after maternal smoking. Maternal heart rate and systolic blood pressure increased 8.7% and 15.0%, respectively, immediately after smoking, while diastolic blood pressure remained unchanged. Fet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Increased basal FHR, returning to the initial level after an average period of 10 min, was observed in both groups immediately after the cigarette smoking; a similar observation was previously reported by others [10].…”
Section: Commentssupporting
confidence: 86%
See 2 more Smart Citations
“…Increased basal FHR, returning to the initial level after an average period of 10 min, was observed in both groups immediately after the cigarette smoking; a similar observation was previously reported by others [10].…”
Section: Commentssupporting
confidence: 86%
“…A transient peripheral vasoconstriction within the fetus may probably lead to the decrease of fetal somatic activity. Increased mean FHR levels and reduction of short-term variability are probably related not only to the increased placental resistance but also to other acute hemodynamic changes, such as the decrease in left ventricular systolic and diastolic diameters unassociated to significant modifications in stroke volume or cardiac output observed by SORENSEN and BORLUM [10].…”
Section: Commentsmentioning
confidence: 92%
See 1 more Smart Citation
“…Similarly, Barutçu et al reported that acute smoking caused a significant change in both left and right ventricular diastolic function in healthy adults [30]. Sorensen and Borlum reported that acute maternal smoking caused a temporary increase in fetal heart rate, however, no significant change in fetal cardiac functions [31]. ICT, as an indication of systolic dysfunction, and IRT, as an indication of diastolic dysfunction, were found significantly high in this study and thus it may be suggested that both systolic and diastolic left ventricular functions of the fetuses exposed to chronic smoking during pregnancy were affected.…”
Section: Discussionmentioning
confidence: 93%